Osteotome-Mediated Sinus Lift without Grafting Material: A Review of Literature and a Technique Proposal. (7th May 2012) - Taschieri, Silvio; Corbella, Stefano; Saita, Massimo; Tsesis, Igor; Del Fabbro, Massimo
Abstract : Implant rehabilitation of the edentulous posterior maxilla may be a challenging procedure in the presence of insufficient bone volume for implant placement. Maxillary sinus augmentation with or without using grafting materials aims to provide adequate bone volume. The aim of the present study was to systematically review the existing literature on transalveolar maxillary sinus augmentation without grafting materials and to propose and describe an osteotome-mediated approach in postextraction sites in combination with platelet derivative. The systematic review showed that high implant survival rate (more than 96% after 5 years) can be achieved even without grafting the site, with a low rate of complications. Available alveolar bone height before surgery was not correlated to survival rate. In the described case report, three implants were placed in posterior maxilla after extraction of two teeth. An osteotome-mediated sinus lifting technique was performed with the use of platelet derivative (PRGF); a synthetic bone substitute was used to fill the gaps between implant and socket walls. No complications occurred, and implants were successfully in site after 1 year from prosthetic loading. The presented technique might represent a viable alternative for the treatment of edentulous posterior maxilla with atrophy of the alveolar bone though it needs to be validated by studies with a large sample size.